2011
DOI: 10.1111/j.1600-0625.2011.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase inhibitors block the acceleration of skin permeability barrier repair by red light

Abstract: We previously demonstrated that exposure to red light (550-670 nm) accelerates epidermal permeability barrier recovery after barrier disruption. Furthermore, we showed that photosensitive proteins, originally found in retina, are also expressed in epidermis. In retina, transducin and phosphodiesterase 6 play key roles in signal transmission. In this study, we evaluate the role of phosphodiesterese 6 in the acceleration by red light of epidermal permeability barrier recovery. Immunohistochemical study and rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In retina, transducin and phosphodiesterase 6 play key roles in signal transmission. Thus, we hypothesized that these proteins might exist in epidermal keratinocytes and be associated with barrier homeostasis (Goto 2011). Immunohistochemical study and reverse transcription-PCR assays confirmed the expression of both transducin and phosphodiesterase 6 in epidermal keratinocytes.…”
Section: Visible Lightmentioning
confidence: 96%
“…In retina, transducin and phosphodiesterase 6 play key roles in signal transmission. Thus, we hypothesized that these proteins might exist in epidermal keratinocytes and be associated with barrier homeostasis (Goto 2011). Immunohistochemical study and reverse transcription-PCR assays confirmed the expression of both transducin and phosphodiesterase 6 in epidermal keratinocytes.…”
Section: Visible Lightmentioning
confidence: 96%
“…In addition to these more ‘traditional’ downstream cascades, new intriguing insights are emerging in the literature. Interestingly, red light has been reported to induce rhodopsin‐mediated, phosphodiesterase‐dependent recovery of skin barrier function . In contrast, violet light of 410 nm suppresses human epidermal keratinocyte differentiation by the activation of rhodopsin, probably involving specific signalling pathways via Gitalicαi .…”
Section: Multiple Downstream Biomolecular Reactions Explaining Physiomentioning
confidence: 99%
“…Red-light-induced acceleration of the barrier recovery was blocked by a phosphodiesterase-6 inhibitor. 93 These results suggest that the photoreceptors and signal transmission system present in the retina are also functionally expressed in epidermal keratinocytes.…”
Section: Visible Radiationmentioning
confidence: 87%